Paul, Apostle of God's glory in Christ: a Pauline theology - Schreiner, Thomas R. (InterVarsity Press, 2001)
Every serious student of the New Testament and of Christian theology must come to grips with the apostle Paul and his theology. By any measure, Paul's theological formulations of justification by faith, the meaning of the cross, the nature of the church, the preexistence and incarnation of Christ, and the future consummation of the new creation have been fundamental building blocks of Protestant theology. In Paul, Apostle of God's Glory in Christ,Thomas R. Schreiner gives us a sound and insightful exposition and assessment of Paul's theology that is well geared to the needs of seminary students and working pastors. While thoroughly informed by the issues of contemporary Pauline studies, he offers an account of Paul's theology that is relatively unburdened by scholarly trappings but deals directly with the matter at hand. "The goal of writing a Pauline theology," he writes, "is to unearth Paul's worldview and to present it to contemporaries. Our task is not merely to reproduce Paul's thinking on various topics but to rightly estimate what is most important in his thinking and to set forth the inner connections between the various themes." Like most writers of a Pauline theology, Schreiner discerns something at the heart and soul of Paul's theology. The theme is captured in the title of the book, Paul, Apostle of God's Glory in Christ. As Schreiner puts it, "The passion of Paul's life, the center and foundation and capstone of his vision, and the animating motive of his mission was the supremacy of God in and through the Lord Jesus Christ." Schreiner has stitched this theme into the fabric of his book, and the result is a Pauline theology that is not only informative but spiritually uplifting as well. Here is a Pauline theology eminently suited to the needs of theological students and preachers.